PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR TANAOBA LAIS MANEKAT - Laa , Nana Arwana Milenia; Susanto, Andi Heru (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study is quantitative research that aims to determine the influence of transformational leadership variables and motivation on employee performance variables. The sample used was 100 employees of PT BPR Tanaoba Lais Manekat with a questionnaire instrument. Instrument quality testing is carried out through validity tests and reliability tests. The data analysis method uses descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results showed that, H₁ is accepted which means transformational leadership has a positive and significant effect on employee performance. H₂ is accepted which means motivation has a positive and significant effect on performance. H₃ is accepted which means transformational leadership and motivation variables simultaneously have a positive and significant effect on employee performance. In this study, only examined the variables of transformational leadership and motivation, so there are other variables that affect employee performance that were not included in this study.